Pb-Nd-Sr Isotope Geochemistry of Metapelites from the Iberian Pyrite Belt and Its Relevance to Provenance Analysis and Mineral Exploration Surveys - Luz, Filipa (2022)
The Iberian Pyrite Belt is a world-class metallogenic district developed at the Devonian-Carboniferous boundary in the Iberian Variscides that currently has seven active mines: Neves Corvo (Cu-Zn-Sn) and Aljustrel (Cu-Zn) in Portugal, and Riotinto (Cu), Las Cruces (Cu), Aguas Teñidas (Cu-Zn-Pb), Sotiel-Coronada (Cu-Zn-Pb), and La Magdalena (Cu-Zn-Pb) in Spain. The Iberian Pyrite Belt massive sulfide ores are usually hosted in the lower sections of the volcano-sedimentary complex (late Famennian to late Visean), but they also occur in the uppermost levels of the phyllite-quartzite group at the Neves Corvo deposit, stratigraphically below the volcano-sedimentary complex. A Pb-Nd-Sr isotope dataset was obtained for 98 Iberian Pyrite Belt metapelite samples (from Givetian to upper Visean), representing several phyllite-quartzite group and volcano-sedimentary complex sections that include the footwall and hanging-wall domains of ore horizons at the Neves Corvo, Aljustrel, and Lousal mines. The combination of whole-rock Nd and Sr isotopes with Th/Sc ratios shows that the siliciclastic components of Iberian Pyrite Belt metapelites are derived from older quartz-feldspathic basement rocks (–11 ≤ εNdinitial ≤ –8 and (87Sr/86Sr)i up to 0.727). The younger volcano-sedimentary complex metapelites (upper Tournaisian) often comprise volcanic-derived constituents with a juvenile isotopic signature, shifting the εNdi up to +0.2. The Pb isotope data confirm that the phyllite-quartzite group and volcano-sedimentary complex successions are crustal reservoirs for metals found in the deposits. In Neves Corvo, where there is more significant Sn- and Cu-rich mineralization, the higher (206Pb/204Pb)i and (207Pb/204Pb)i values displayed by phyllite-quartzite group and lower volcano-sedimentary complex metapelites (up to 15.66 and 18.33, respectively) suggest additional contributions to the metal budget from a deeper and more radiogenic source. The proximity to Iberian Pyrite Belt massive sulfide ore systems hosted in metapelite successions is observed when (207Pb/204Pb)i >15.60 and Fe2O3/TiO2 or (Cu+Zn+Pb)/Sc >10. These are important criteria that should be considered in geochemical exploration surveys designed for the Iberian Pyrite Belt.